Building green : environmental architects and the struggle for sustainability in Mumbai - Rademacher, Anne (University of California Press, 2018)
The author explored the experience of environmental architects in Mumbai, one of the world's most populous and population-dense urban areas and a city iconic for its massive informal settlements, extreme wealth asymmetries, and ecological stresses, by examining the training and experience of these architects.